2016
DOI: 10.1262/jrd.2016-002
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the effect of lipopolysaccharide on tumor necrosis factor α (TNF-α) secretion and <i>TNF</i> and <i>TNFR1</i> mRNA levels in feline endometrium throughout the estrous cycle during pyometra and after medroxyprogesterone acetate treatment

Abstract: Endotoxins released by Gram-negative bacteria are potent stimulators of tumor necrosis factor α (TNF-α) production. The objectives of this study were to evaluate plasma levels of TNF-α, TNF-α secretion, and mRNA levels of TNF and TNF-α receptor type 1 (TNFR1) following exposure to lipopolysaccharide (LPS). For this, we used cultured endometrial cells or organ cultures, throughout the estrous cycle, after hormone treatment with medroxyprogesterone acetate (MPA), and during pyometra. Plasma TNF-α concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
(45 reference statements)
0
4
0
Order By: Relevance
“…In addition, TNFα and lipopolysaccharide (LPS) increase the in vitro expression of Toll-like receptors (TLRs) 2 and 4 in the endometrial explants of cats in the estrus or those treated with P 4 , thus suggesting the participation of TLRs in pyometra of cats [163], as also demonstrated by Jursza-Piotrowska and Siemieniuch [29]. Activation of these receptors is important for triggering the innate immune response, which is an essential cellular defense mechanism in bacterial infections such as pyometra.…”
Section: Uterus and Placentamentioning
confidence: 75%
See 2 more Smart Citations
“…In addition, TNFα and lipopolysaccharide (LPS) increase the in vitro expression of Toll-like receptors (TLRs) 2 and 4 in the endometrial explants of cats in the estrus or those treated with P 4 , thus suggesting the participation of TLRs in pyometra of cats [163], as also demonstrated by Jursza-Piotrowska and Siemieniuch [29]. Activation of these receptors is important for triggering the innate immune response, which is an essential cellular defense mechanism in bacterial infections such as pyometra.…”
Section: Uterus and Placentamentioning
confidence: 75%
“…Studies conducted in the last decade with domestic cats have shown that several growth, hormonal, immunological, and redox factors are expressed differently in the uterus and ovary throughout the reproductive cycle [14,[18][19][20][21][22][23][24][25], as well as in the placenta throughout pregnancy [18,19,26,27]. Moreover, these studies show that changes in the expression of some of these factors are involved in the reproductive alterations observed in pyometra [14,[28][29][30] and in feline immunodeficiency virus (FIV) infection [31][32][33][34]. Thus, this paper reviews the current knowledge about the modulation and expression profiles of hormonal, immunological, redox, and growth mediators in the uterus, ovary, and placenta of domestic cats throughout the estrous cycle and during pregnancy.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…Numerous studies have demonstrated that treatment with endotoxin or LPS results in an increase of TNF-α production. Jursza-Piotrowska and Siemieniuch [52] had conducted a study to determine whether the epithelial or the stromal cells are responsible for the release of TNF-α. Their study has shown that the exposure of LPS on feline endometrial cell in vitro significantly increases the release of TNF-α by endometrial epithelial cells, but not the stromal cells.…”
Section: Correlation Of Pro-inflammatory Cytokines During Bacterial Amentioning
confidence: 99%